U.K. Inflation and Relative Prices over the Last Decade : How Important was Globalization? - Hunt, Benjamin (IMF Working Papers; Working Paper ;, 2007)
In this paper, the IMF's new Global Economy Model (GEM) is used to estimate the relative importance of a number of factors argued to explain the differences in the trends in core inflation and relative prices in the United Kingdom, the Euro Area and the United States. The simulation results indicate that while the direct effect of globalization has had a larger effect in the United Kingdom than in either the United States or the Euro Area, it explains only a portion of the developments and U.K. specific factors played an important role.